Notes égyptiennes - Bernard Boyaval (Kentron, 2004)
Un fragment de Papyrus en attente : P. Lille 133A note on P. Lille 133 (unpublished).Hèrôdès d’EdfouSome remarks on three metrical epitaphs written by Hèrodès.Quelques formulaires d’expédition de momiesA note on the meaning of formulas such as eis Panopolin, apo Bompaè. vel sim., on mummy-tags.La déclaration des âges sur les kat’oikian apographaiRemarks on age computing in the kat’oikian apographai.Métrique et biométrieOn the metrical background of age computing in Bernand’s Inscriptions métriques.Dioscore « Fils de la Grèce »On the possible meaning of the terms “son of Greece”.Sur une épitaphe doubleA note on the word “epidemic” in the Graeco-Roman Egypt.Note d’onomastique juiveA note about onomastic data from Tell el-Yaoudieh.Les noms de personnes à Tell el-YahoudijehNotes about the proper names given to Jews buried in Tell el-Yahoudijeh area.Le sobriquet PsyllasA note on the nickname Psyllas / Psyllos.Les emplois funéraires de chrestosOn the meanings of chrestos.Les espaces verts du nome oxyrhynchiteSome notes on the Oxyrhynchite gardens and orchards.Sur une vigne grimpanteA note on the word anadendras.La GèroboskiaSome remarks on the gèroboskia.Deux témoins égyptiens de l’audianismeSome remarks on two Greek texts linked with Audius’ theological views.L’intérêt démographique du cimetière copte de Saqqarah-NordNotes on the demographic data in the coptic cemetery at Saqqarah-North (5th-6th centuries A. D.).L’étiquette de TachbelisThe mummy-tag of a young woman named Tachbelis: a note on its historical meaning.Sur la sous-représentation des hommes âgés dans l’épigraphie funéraire de l’Égypte gréco-romaineA note on the lack of older men in Graeco-Roman epitaphs from Egypt.L’épitaphe de Valeria appelée aussi ThermouthisOn a gravestone prose imitating metrical epitaphs.Une originalité de la démographie égyptienne : la représentation villageoiseThe ratio of country people to townspeople in demographic data from Roman Egypt.La taxation des momies à Coptos-estDid seamen convey mummies along the eastern road of Egypt?AteknosA note on the different meanings and ambiguities of the adjective ateknos.